Advances in Communication of Design Proceedings of the AHFE 2017 International Conference on Human Factors in Communication of Design, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Ho, Amic G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book focuses on the emerging role of human factors in understanding, communicating with and engaging users. It reports on innovative approaches, with a special emphasis to visuals cues, such as new typographies, geometries and graphics for mobile and computer interfaces. The book also cover topics of image and video processing, user-focused data compression, generative visuals, computational photography, and interactive design. Further topics include creative and empathetic design, human touch in digital graphics and experiential graphics. Based on the AHFE 2017 International Conference on Human Factors in Communication of Design, held on July 17-21, 2017, in Los Angeles, California, USA, this book reports on new findings, best-practices and case studies, providing readers with a fresh perspective and novel insights into the applications of human factors for enriching communication of design to users.
Humanistic teaching approaches in typographic communication design -- Directing untrained users' attention using simple sound patterns -- Looking forward to reverse image search: Measuring the effectiveness of reverse image searches in online help -- Teaching methodologies in communication design -- Ergonomics and organizational communication: Methods for business communication auditing -- Trust building privacy preferences for young adults visiting political campaign websites -- The style of imagery: A color study of landscape paintings -- The effectiveness of message sidedness on trust in check-in advertising -- Towards a generalization of new media -- Calligraphy practice app, system and tool for learning calligraphy -- Smart device-based notifications: A survey on user's satisfaction of traditional notification mechanisms -- The challenge of online meal ordering platforms: Website design and credibility, customers' trust, and food safety -- Consistency of visual information in web design: Focusing on responsiveness of a university website -- Awareness collaboration with uses and designers: Metaphor analysis and expression of spatial image schemes with sign language. .
Keywords: Engineering design; Psychology; User interfaces (Computer systems).; Human-computer interaction; Human-machine systems; Engineering Design; Behavioral Sciences and Psychology; User Interfaces and Human Computer Interaction; Interaction Design